HAEMATO - BIOCHEMICAL AND HISTOLOGICAL CHANGES UPON SUPPLEMENTED EXTRUDED FABA BEAN (VICIA FABA L.) FEEDING IN RATS - Rajawat, Prakrati; Bhatele, Aarti; Kushwah, Ameeta (Indian Journal of Veterinary Sciences and Biotechnology, 2010)
Supplementation of extruded faba bean (EFB) in cereals diet as a protein source improved the content of RBC, PCV and haemoglobin in weaning albino rats and decreased cholesterol level No severe deleterious effect on the structural components of parenchymatous tissues was observed; architectural pattern was well maintained. Higher supplementation of EFB at 40% in diet did not prove beneficial and effective as compared to its 20% supplementation and therefore, not recommended.